Health and wellbeing boards: public health decision making bodies or political pawns?. (February 2017) - Greaves, Z.; McCafferty, S.
Abstract: Objectives: Health and Wellbeing boards in England are uniquely constituted; embedded in the local authorities with membership drawn from a range of stakeholders and partner organizations. This raises the question of how decision making functions of the boards reflects wider public health decision making, if criteria are applied to decision making, and what prioritization processes, if any, are used. Methods: Qualitative research methods were employed and five local boards were approached, interview dyads were conducted with the boards Chair and Director of Public Health across four of these ( n  = 4). Three questions were addressed: how are decisions made? What are the criteria applied to decision making? And how are criteria then prioritized? A thematic approach was used to analyse data identifying codes and extracting key themes. Results: Equity, effectiveness and consistency with strategies of board and partners were most consistently identified by participants as criteria influencing decisions. Prioritization was described as an engaged and collaborative process, but criteria were not explicitly referenced in the decision making of the boards which instead made unstructured prioritization of population sub-groups or interventions agreed by consensus. Conclusions: Criteria identified are broadly consistent with those used in wider public health practice but additionally incorporated criteria which recognizes the political siting of the boards. The study explored the variety in different board's approaches to prioritization and identified a lack of clarity and rigour in the identification and use of criteria in prioritization processes. Decision making may benefit from the explicit inclusion of criteria in the prioritization process. Highlights: Board's criteria are broadly consistent with those of wider public health practice. Additional criteria showed respect of needs of partners and increased public focus. Boards lack clarity and rigour in the use of criteria in prioritization processes. Boards would strategically benefit from explicit use of criteria in prioritization.